2013
DOI: 10.1017/s1355617713001203
|View full text |Cite
|
Sign up to set email alerts
|

Visual Motion Processing and Visual Sensorimotor Control in Autism

Abstract: Impairments in visual motion perception and use of visual motion information to guide behavior have been reported in autism, but the brain alterations underlying these abnormalities are not well characterized. We performed functional magnetic resonance imaging (fMRI) studies to investigate neural correlates of impairments related to visual motion processing. Sixteen high-functioning individuals with autism and 14 age and IQ-matched typically developing individuals completed two fMRI tasks using passive viewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…The second finding entailed a hemi‐field open loop deficit indicating dysfunction in left extra‐striate areas or pathways carrying visual motion information forward to sensorimotor areas. A recent fMRI study of two pursuit tasks investigating the neural basis of these deficits in visual motion processing and visual sensorimotor control in autism confirmed local alterations in V5 circuitry and reduced top down modulation of sensory processing in V5 [Takarae, Luna, Minshew, & Sweeney, ].…”
Section: Discussionmentioning
confidence: 87%
“…The second finding entailed a hemi‐field open loop deficit indicating dysfunction in left extra‐striate areas or pathways carrying visual motion information forward to sensorimotor areas. A recent fMRI study of two pursuit tasks investigating the neural basis of these deficits in visual motion processing and visual sensorimotor control in autism confirmed local alterations in V5 circuitry and reduced top down modulation of sensory processing in V5 [Takarae, Luna, Minshew, & Sweeney, ].…”
Section: Discussionmentioning
confidence: 87%
“…One possibility, suggested by single cells recordings, is that a reduced surround inhibition in our ASD group is caused by the atypically weak feedback signal from MT. However, arguing against this suggestion, fMRI studies with ASD individuals found that their activation of MT/V5 motion area was not altered during forced-choice motion discrimination task (Robertson et al, 2014), or was even atypically enhanced during passive viewing of drifting ripple pattern (Schwarzkopf et al, 2014; Takarae et al, 2014). A more feasible explanation based on animal studies suggests the low effectiveness of the “near-surround” inhibitory signal in primary visual cortex of individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…During visual motion perception, greater activation and faster hemodynamic decay was seen in V5/MT, suggesting reduced inhibitory modulation(126). During passive language processing, negative BOLD responses were reduced in ASD, suggesting failure of inhibitory processes to induce regional deactivation(127).…”
Section: Functional Neuroimagingmentioning
confidence: 99%